Atomistic insight into hydrogen trapping at MC/BCC-Fe phase boundaries: The role of local atomic environment. (15th April 2021) - Zhang, Boning; Su, Jie; Wang, Maoqiu; Liu, Zhenbao; Yang, Zhigang; Militzer, Matthias; Chen, Hao
Abstract: A physical understanding of hydrogen trapping at microstructural defects such as grain boundaries ( GBs ) and phase boundaries ( PBs ) is vitally important for the design of hydrogen embrittlement (HE) resistant metals. As compared with GBs, the mechanism of hydrogen trapping at PBs is rather unclear due to the complex atomic environment at PBs . We perform systematic density functional theory (DFT) calculations to reveal the physical origin of hydrogen trapping at a variety of PBs between body centered cubic ( BCC )-Fe and NaCl-type carbides ( MCs ). It is found that hydrogen trapping energetics at MC/BCC-Fe PBs depend not only on local volume dilation of the hydrogen trapping sites, but also on their local atomic environment. An array of descriptors such as lattice strain, geometric volume, and charge density, which has been proven to effectively predict hydrogen trapping at GBs, fail to quantify hydrogen trapping at MC/BCC-Fe PBs . We analyzed the electronic interactions at PBs and found that they are closely related to hydrogen binding energies, and the Bader volume of hydrogen is a universal descriptor for assessing hydrogen trapping energetics at PBs . This study provides new insight into hydrogen trapping at microstructural defects from atomic and electronic scales, and is aimed to advance the future design of hydrogen traps and HE resistant metals. Graphical abstract: Image, graphical abstract